Mechanisms and recent advances in the diagnosis and treatment of nitrous oxide-induced peripheral neuropathy: a narrative review - Zou, Xiaodi; Yi, Fangyu; Zhou, Weijie; Dong, Yanzhao; Alhaskawi, Ahmad; Zhou, Haiying; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Abdulla, Mohamed Hasan Abdulla Hasan; Alenikova, Olga; Abdalbary, Sahar Ahmed; Lu, Hui; et al. (Frontiers in Neurology, 2024)
Under standard conditions, nitrous oxide (N 2 O) manifests as a colorless, odorless gas with a mildly sweet taste. The compound is utilized in a diverse array of applications finds applications in various fields, including its incorporation in use as an aerosol propellants, usage as an accelerant in motor racing, and as an anesthetic in surgical procedures and dentistry. dentistry.Unfortunately, the recreational misuse of N2O has become prevalent among young individuals due to its euphoric and hallucinogenic effects. Compounding this issue is the fact that nitrous oxide can be easily obtained from over-the-counter household items, facilitating its non-medical use. The global community has witnessed a surge in the recreational utilization of nitrous oxide gas in recent years. Despite the widespread non-medical abuse of N2O, there remains inadequate understanding of the potential adverse effects resulting from exposure to it. This paper provides an overview of management findings, laboratory and electrodiagnostic characteristics, as well as clinical presentations associated with neurological disorders induced by nitrous oxide usage.Regrettably, the euphoric and hallucinogenic effects of N 2 O have also led to its recreational misuse, particularly among the youth demographic. Compounding the issue, nitrous oxide can be sourced from a variety of over-the-counter household items, thereby facilitating its non-medical use. The global community has observed a surge in the recreational utilization of nitrous oxide gas over recent years. Despite the widespread non-medical abuse of N 2 O, the potential adverse effects resulting from exposure remain inadequately understood. This paper offers an overview of the management findings, laboratory and electrodiagnostic characteristics, and clinical presentations associated with nitrous oxide-induced neurological disorders.